Trainee teachers' experience of primary science teaching, and the perceived impact on their developing professional identity. Issue 4 (8th August 2018) - Blackmore, Karen; Howard, Colin; Kington, Alison
Abstract: This study took place within an environment of educational change in teaching and assessment in the UK, where the National Curriculum (NC) and National External Examination syllabi undertook significant revision. Science education specifically, has seen aspiration raised to allow pupils to achieve a greater depth of understanding at Key Stage 4 and hence facilitate advanced study. Central to the development of effective scientific understanding is teacher preparation. This study examined the factors that impacted on the experiences of primary teachers during their training. Questionnaires completed by a sample of one hundred and sixteen trainee teachers followed by semi-structured interviews of sixteen trainees were used as a means of interpreting Post-Graduate Certification in Education (PGCE) trainee teachers' experiences during taught university sessions and school based training. The findings showed that the majority of the trainees rated their training highly, and perceived themselves to be confident primary science pedagogues. They felt, however that the very limited opportunities to observe and teach science during their training negatively influenced their overall development.